Alternative performance measures: A~structured literature review of research in academic and professional journals - Sascha B. Herr; Peter Lorson; Jochen Pilhofer (Schmalenbach Journal of Business Research (SBUR), 2022)
For more than two decades, the reporting of so-called 'alternative performance measures' (APMs) has been a~common phenomenon in external financial reporting. APMs are voluntarily disclosed and generally unaudited performance measures. Typically, APMs modify earnings measures calculated in accordance with generally accepted accounting principles (GAAP) by (subjectively) adjusting certain earnings components. In the academic literature, with the information motive on the one hand and the motive of (adversarial) investor influence on the other hand, two alternative explanations for the voluntary reporting of alternative performance measures are discussed, which are difficult, if not impossible, for external stakeholders to disentangle. Taking into account the recent developments in more than 250 published articles in the last decade, this paper critically reviews a~wide range of literature from the United States (U.S.), Europe and, to a~less extent, Australia/Asia. In particular, we analyse a~comprehensive sample of more than 400 research papers published in academic and professional journals as well as other publications which are important in the academic discourse. The purpose of this paper is to identify relevant research gaps that provide starting points for future research. For this purpose, our methodological approach strictly follows structured literature review (SLR) methodology in order to minimise researcher idiosyncrasies. Thus, our SLR facilitates a~decided derivation of research gaps based on a~reliable and valid analytical framework which has been deductively derived from previous research.
Keywords: 650; Adjusted earnings; Alternative performance measures; Non-GAAP (financial) measures; Pro forma earnings; Street earnings; Structured literature review